Perlindungan Hukum Terhadap Upah Pekerja di PT Widyaloka Jaya Perkasa Kota Jambi Berdasarkan Peraturan Ketenagakerjaan - Arsyadi , Khavy; Yetniwati, Yetniwati; Fathni, Indriya (Zaaken: Journal of Civil and Business Law, 2026)
This study aims to analyze the legal protection given to workers related to the right to wages at PT Widyaloka Jaya Perkasa and to identify the obstacles faced in the implementation of the rights to wages of workers. The formulation of the problem in this study is: How is the legal protection of the rights to wages of workers at PT Widyaloka Jaya Perkasa based on the Manpower Regulation and What are the obstacles in the implementation of workers' rights to wages at PT Widyaloka Jaya Perkasa Based on the Manpower Regulation. This study uses an empirical legal method with a descriptive approach, involving interviews with employees and analysis of related documents. The results of the study show what aspects of the problems in the implementation of the right to wages at PT Widyaloka Jaya Perkasa need to be observed and studied so that there are no violations of the law that occur after the existence of laws and regulations related to employment. These aspects include legal protection and what are the obstacles in the implementation of the rights to wages of workers.